THE DISCOURSE ON CONTEMPORARY TA’LÎL AL-HADITH: The Thoughts of al-Ḥuwaynî, Mamdûḥ, and al-Malîbârî - Nursyahbani, Iqbal; Hasbillah, Ahmad 'Ubaydi; Farid, Mohamad (Ulul Albab: Jurnal Studi Islam, 2025)
Taʿlīl al-ḥadīth—the critical investigation of hidden defects in prophetic reports—has been practiced since the formative period of Islamic scholarship and has undergone renewed expansion since the mid-14th/20th century. In this contemporary phase, distinct methodological orientations have emerged around leading figures such as Abū Isḥāq al-Ḥuwaynī (Salafī), Saʿīd Mamdūḥ (Ashʿarī-traditionalist), and Ḥamzah al-Malībārī (Iḥyāʾ Manhaj al-Mutaqaddimīn). This article presents a comparative analysis of their thought, utilizing library research and thematic interpretation, and highlights the methodological, epistemological, and socio-religious implications of current debates. The study argues that contemporary discourse on taʿlīl al-ḥadīth is no longer confined to technical isnād criticism but has become a site of ideological contestation and the renegotiation of religious authority within global Muslim communities. Al-Ḥuwaynī rejects tafarrod (solitary transmission) as a valid ʿillah and emphasizes strict muʿāṣarah (narrator contemporaneity); Mamdūḥ also rejects tafarrod but fully accepts ziyādat al-thiqah (trustworthy narrators’ additions); whereas al-Malībārī regards all ʿilal as potentially qādiḥah (damaging) and widens criticism to include weak transmitters. These positions implicitly respond to pressing contemporary concerns: al-Ḥuwaynī to the global spread of Salafism, Mamdūḥ to sectarian tensions and calls for social justice, and al-Malībārī to rising spiritual disorientation and permissive cultural trends. By mapping these orientations and their implications for academic scholarship, religious practice, and communal dynamics, this article highlights the need to reassess taʿlīl al-ḥadīth as both a technical discipline and a significant influence on shaping authority, orthodoxy, and Muslim public life today. The study thus contributes a critical framework for understanding the evolving epistemology of ḥadīth criticism in the modern era.